Distancia y representación en la administración de justicia. Córdoba en el último cuarto del siglo XVI. - González Navarro, Constanza (Memoria Americana, 2023)
The administration of justice in the colonial period implied the participation of a varied set of agents -judges, notaries, secretaries, attorneys, lawyers, etc.- that guaranteed the exercise of jurisdiction. This paper highlights the relevance of attorneys -as representatives of third parties- in the administration of justice based on a voluminous corpus of public deeds created in the city of Córdoba in the late 16th century. Based on the survey of powers of attorney granted between 1574 and 1600, the analysis focuses on those whose granting specifically involved the power to manage judicial matters, trying to account for some of the characteristics and variants of the representation, such as the geographical scope of the actions of the proxies and the participation of different social sectors in this type of intermediation.